Comparative Analysis of Computed Tomography and Laparoscopy Data in Preoperative Staging of Gastric Cancer - N. K. Silanteva; T. A. Аgababyan; A. A. Kholeva; V. Yu. Skoropad; Z. N. Shavladze; S. A. Ivanov; L. P. Zhavoronkov (Вестник рентгенологии и радиологии)
Objective: to compare the data of computed tomography (CT) and diagnostic laparoscopy (DL) in the preoperative estimation of the extension of gastric cancer.Material and methods. Data on 51 patients with a histologically confirmed diagnosis of gastric cancer were analyzed. CT and DL were performed in all the patients at an interval of 1–2 days during their preoperative examinations to determine the stage of a tumor process. Of the 51 patients, 34 (66.7%) were found to have no distant abdominal metastases and underwent radical surgery. CT and DL revealed distant abdominal organ metastases in 17 (33.3%) of the 51 patients. To evaluate the diagnostic efficiency of CT and DL, the investigators calculated the main characteristics (sensitivity, specificity) and auxiliary criteria (accuracy, positive (PPV) and negative (NPV) predictive values.Results. The findings suggested that the diagnostic efficiency of CT in determining the T category was a sensitivity of 86% and a specificity of 92%; and that of DL was 83% and 87%, respectively. CT in diagnosing a regional lymph node metastasis had a higher sensitivity than DL (88% vs. 63%), but a lower specificity than DL (80% vs. 90%). CT diagnosis of peritoneal carcinomatosis exhibited a sensitivity of 46%, a specificity of 97.4%, an accuracy of 84.3%, PPV of 85.7%, and NPV of 84.1%. The symptoms of peritoneal carcinomatosis were ascites, soft tissue nodules along the peritoneum, diffuse induration and thickening of abdominal tissue planes, and increased mesenteric vascularity.Conclusion. The combined use of CT and DL is a current algorithm for examining patients with gastric cancer. It makes it possible to obtain complete information about the extension of the process, to increase the accuracy of preoperative diagnosis and to form a group of patients to undergo radical surgery.